Administrative Mechanism of Joint Participation and Cooperation in the Early Stages of the COVID-19 Outbreak in Wuhan - Yan J; Zhao D (Dove Medical Press, 2020)
Jingjing Yan,1 Dahai Zhao1,2 1School of International and Public Affairs, Shanghai Jiao Tong University, Shanghai, People’s Republic of China; 2Shanghai Jiao Tong University-Yale University Joint Center for Health Policy, Shanghai, People’s Republic of ChinaCorrespondence: Dahai ZhaoSchool of International and Public Affairs, Shanghai Jiao Tong University, No. 1954 Huashan Road, Shanghai 200030, People’s Republic of ChinaTel +86 139-1896-8766Email dahaizhao@sjtu.edu.cnIntroduction: From December 2019 to January 2020, a novel coronavirus disease (officially COVID-19) was reported in Wuhan and continued to spread all China. This study describes the administrative mechanism of joint participation and cooperation during the early stages of the COVID-19 outbreak in Wuhan and the rest of the country by health practitioners and administrative authorities.Methods: This study adopted a qualitative design. An analytical framework based on the theory of policy participation that included stimulus, setting, and position of policy participation was constructed. Qualitative data of policy participation by health practitioners and administrative authorities consisted of publicly available data.Results: Early during the outbreak, from December 2019 to January 2020, three main stages occurred according to the containment situation. The first stage was characterized by limited knowledge of the transmission dynamics of the virus and a consequently weak response. In the second stage, the disease spreads rapidly because of travel during a national festival. In the third stage, particularly when top Chinese leaders delivered instructions to intensify containment efforts, diverse departments initiated joint prevention and control measures to combat COVID-19.Conclusion: The administrative mechanism of joint participation and cooperation was instrumental in avoiding a substantial increase in both cases and fatalities in the initial stage of the outbreak. This joint participation provides valuable experience and initiatives for major public health emergency preparedness, and the new empirical evidence further highlights the importance of policy participation theory in epidemic prevention in other countries.Keywords: joint administration, coronavirus disease 2019, public health emergency, policy participation